"Did you get placed with all white ladies in your group?": reflections on co-creating an anti-racist social work (virtual) classroom. Issue 1 (2nd January 2022) - Lerner, Justin Evan
ABSTRACT: As a white social work instructor and therapist committed to anti-racist practice, I reflect on my experiences teaching group work virtually during a pandemic. I provide an example of how I inadvertently perpetuated white supremacy through a mistake I made in creating groups that isolated students of color. I discuss how I addressed this mistake with the class and worked with the students to co-create an anti-racist and anti-oppressive classroom setting through our group process. I offer strategies for how I will continue to deepen group processes centered in anti-racist practices, such as building trust through transparency, acknowledging mistakes, including opportunities for race caucuses, and creating continual optional check-ins with students of color in order to maximize and center their learning in my courses.